The soil resources of tropical Africa : a symposium of the african studies association of the United Kingdom - Moss, Rowland Percy (Cambridge, London : Cambridge University Press, 1968)
This volume are papers given at the symposium on the soil resources of tropical Africa held at University college London, it is clear that the material of both the paper and the discussion would make a useful addition to the published literature on African soil.
Includes bibliographical references and index.
hza 29/01/2019
Loans
Keywords: Soil science; Soils; Africa